A single-centre observational study comparing the impact of different cytomegalovirus prophylaxis strategies on cytomegalovirus infections in kidney transplant recipients. (June 2021) - Tan, Mabel Si Hua; Chung, Shimin Jasmine; Ho, Quan Yao; Thangaraju, Sobhana; Kee, Terence Yi Shern
Background/objective: Prevention of cytomegalovirus (CMV) infection is an important component of post kidney transplant care. We aimed to evaluate the impact of two different CMV prophylaxis protocols on the epidemiology and outcomes of CMV infections at our centre. Methods: This is a single-centre retrospective before/after observational study. Kidney transplant recipients who received Protocol 1, a valacyclovir- or valganciclovir-based regimen prescribed for one to three months based on the CMV risk status between 2004 and 2008, were compared to those who received Protocol 2, a valganciclovir-based regimen prescribed for three months and six months for those at moderate and high risk, respectively, between 2010 and 2014. The impact of different prophylaxis regimens on the incidence of CMV infections, disease, recurrent infections and onset of CMV infection at 24 months were reviewed. Results: There were 192 patients included; 106 patients received Protocol 1, 86 received Protocol 2. At 24 months, the incidence of CMV infection was 53.8% and 55.8% in Protocols 1 and 2, respectively ( p= 0.884). The incidence rates of CMV disease and recurrent CMV infections were higher in Protocol 1, but this was not statistically significant. The median time to first CMV infection was significantly shorter in patients who received Protocol 1: 132 days (interquartile range (IQR) 125–139 days) versus 185 days (IQR 178–192 days), p= 0.001. Both prophylaxis protocols were well tolerated. Conclusion: The incidence of CMV infection was similar in both protocols. Where valganciclovir is not available, valacyclovir may be considered over no prophylaxis. Post-prophylaxis CMV infections are not uncommon, and vigilance for it should be advocated.